Brain-Derived Neurotrophic Factor Secreting Human Mesenchymal Stem Cells Improve Outcomes in Rett Syndrome Mouse Models - Kim, Hyo Jeong; Bayarsaikhan, Delger; Lee, Jaesuk; Bayarsaikhan, Govigerel; Lee, Bonghee (Frontiers in Neuroscience, 2021)
Rett syndrome (RTT) is a severe X-linked dominant neurodevelopmental disorder caused by mutations in the methyl-CpG-binding protein 2 (MECP2) gene; MeCP2 regulates the expression of brain-derived neurotrophic factor (BDNF) and increasing BDNF levels ameliorates RTT symptoms. However, the clinical application of BDNF is limited, because of its short half-life and low penetrance across the blood-brain barrier. In this study, we generated BDNF-secreting mesenchymal stem cells (MSCs) from the human umbilical cord cells, using CRISPR-Cas9. We studied the effects of BDNF-MSCs in MECP2 knockout and MECP2-deficient mice. BDNF-MSCs upregulated the expression of BDNF, pAKT, and pERK1/2 and downregulated that of pp38, both in vitro and in vivo. In our in vivo experiments, BDNF-MSCs increased the body and brain weights in mice. BDNF-MSCs increased the neuronal cell numbers in the hippocampus, cortex, and striatum; in addition, they increased the number of synapses. BDNF-MSCs upregulated BDNF and the activity of BDNF downstream effectors, such as pAKT and pERK ½; this upregulation was persistent. In conclusion, BDNF-MSCs generated using CRISPR-Cas9 could be a therapeutic strategy for treating RTT.